Spectral and Linear Optical Characterization of Organic Laser Dyes Mixture Solution - Noor K. Abdulmutalib (Journal of Global Pharma Technology, 2020)
Spectral and linear optical properties for mixture of compounds Aurintricarboxylic Acid after polymerization (H1) and  Aurintricarboxylic Acid after closer ring (H2), were determined at different concentrations (3* 10-4, 6*10-4 and 9*10-4 ) M in Dimethyl sulfoxide (DMSO) solvent at room temperature. The intensity of absorption range is towards longer wavelengths (red shift); organic laser dyes have a spectrum within range (240-600) nm. Results demonstrate that mixture of laser dyes are effective optical materials when contrasted with single laser dyes. It can be utilized as resonator in cavity lasers.Keywords: Linear and nonlinear properties, Mixture dyes, Optical limiting, And organic laser dyes.